Pengaruh Harga Terhadap Keputusan Pembelian Di Soon Burger Poris - Lauren, Sandy; Sofiani, Sofiani (PolimdoSains, 2023)
ABSTRAK The food & beverage business in Indonesia is currently growing very rapidly, so the level of competition in business is getting higher. High competition makes buyers have several factors that can influence purchasing decisions to choose a restaurant. This study used a quantitative method with a total sample of 94 respondents. With non-probability sampling technique. The data collection for this research used a Google form questionnaire. Furthermore, the data will be analyzed with several tests using SPSS software. The tests used in this study were descriptive analysis, Pearson correlation test, normality test with Kolmogorov Smirnov, heteroscedasticity test, simple linear regression test, coefficient of determination test, and T test. This study shows that the questionnaire used is valid and reliable. The results of the Kolmogorov Smirnov test and heteroscedasticity showed that the data were normally distributed with an Asymp sig value (0.028 > 0.05) and there was no heteroscedasticity. The results of this study also show that there is a significant influence between the price variable on the purchasing decision variable with a Tcount of 4,665 > Ttable of 1,661. the test results of the coefficient of determination show that 59.2% of the price variable influences the purchase decision. Meanwhile, the other 40.8% is influenced by other factors. So it is hoped that Soon Burger Poris Indah can continue to maintain and increase purchasing decisions through price development. As well as, the continuous development of new innovations in order to attract customers. Key Word: Effect, Price, Buying intention